PERSEPSI RISIKO PADA PEKERJA KONSTRUKSI PENATAAN KAWASAN PURA BESAKIH PADA MASA PANDEMI COVID-19 TAHUN 2022 - Sutarsa, I Nyoman; Pratama, I Putu Eka Yayang (ARCHIVE OF COMMUNITY HEALTH, 2024)
The construction sector is one sector that has a fairly high risk of accidents and occupational diseases. One of the causes of work accidents in the construction sector is the low use of personal protective equipment which is determined by the perception of the risk of work accidents by workers in the workplace. The purpose of this study was to determine the perception of risk among construction workers in the Besakih Temple area arrangement project during the COVID-19 pandemic. This study uses a qualitative research design with a phenomenological approach to be implemented in the construction project of the Besakih Temple Area, Rendang, Karangasem, Bali. Research informants were determined by purposive sampling as many as 13 informants. In addition, triangulation data sources for the validity of research data. The results, perceived risk in the work environment is the risk of physical accidents, financial risks, and COVID-19 risks. Successful sources of risk come from individuals, the environment, and unforeseen circumstances. The main reasons for using PPE are the obligations and awareness of workers, while the reasons for not using PPE are feeling safe, forgetting, uncomfortable, not getting information, and habits in previous projects. This study found that the risk literacy of construction workers is still limited. Suggestions that can be given are in the form of providing more innovative training and morning briefing activities and increasing the visibility of the management in risk mitigation. Keywords: perceive risk, personal protective equipment, construction